A study of eco-conscious consumer behavior on green products - Tan, Sze Ting (2024)
Over 90% of Malaysians are aware of the environmental issue yet reluctant to shift their buying behaviour. The purpose of this study is to examine the relationship between independent variables (Attitude, Subjective Norms, Perceived Behaviour Control, Positive Context, and Negative Context) and the dependent variable (Eco-Conscious Consumer Behaviour) through the integration of Theory of Planned Behaviour (TPB) and Attitude-Behavioural-Context Theory (ABC). A total of 330 questionnaires were distributed through Google Forms to the residents in Kuala Lumpur and Selangor, Malaysia, and IBM SPSS software was employed for data analysis. The data collected were analysed using the Cronbach Alpha Pilot Test, Descriptive Analysis, Pearson Correlation Coefficient Analysis, and Multiple Linear Regression. The result proved that EcoConscious Consumer Behaviour is influenced by Attitude, Subjective Norms, and Positive Context. Eventually, this research had several limitation, and recommendations were provided for future research.